2004
DOI: 10.1177/172460080401900406
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cathepsin H as a Potential Prognostic Marker in Patients with Colorectal Cancer

Abstract: Cathepsin H is a lysosomal cysteine protease that may participate in tumor progression. In order to evaluate its potential as a prognostic marker, its protein levels were measured by ELISA in preoperative sera from 324 patients with colorectal cancer. The level of cathepsin H was significantly increased in patient sera, the median level was 8.4 ng/mL versus 2.1 ng/mL in 90 healthy blood donors (p < 0.0001). A weak association of cathepsin H levels was found with patient age (p = 0.02) but not with Dukes' stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Downregulation of cathepsin H is consistent with other cancers, like cervical cancer 28 and melanoma, where the expression of cathepsin H was inversely related to the invasive potential of the tumor 29. In colorectal cancer high carcinoembryonic antigen (CEA) and low cathepsin H expression correlated with poor prognosis 30. An upregulation of cathepsin H, on the other hand, was found in bladder carcinomas 31 and basal cell carcinomas 32.…”
Section: Discussionsupporting
confidence: 66%
“…Downregulation of cathepsin H is consistent with other cancers, like cervical cancer 28 and melanoma, where the expression of cathepsin H was inversely related to the invasive potential of the tumor 29. In colorectal cancer high carcinoembryonic antigen (CEA) and low cathepsin H expression correlated with poor prognosis 30. An upregulation of cathepsin H, on the other hand, was found in bladder carcinomas 31 and basal cell carcinomas 32.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, cathepsin L levels were increased in sera of patients with pancreatic [ 180 ] and liver cancers [ 181 ]. Serum cathepsin H levels were found to be increased in patients with lung [ 182 ], melanoma [ 183 ], and colorectal cancers [ 184 ]. The findings of these recent studies have alluded to a potential of utilizing cathepsins as biomarkers of cancer though few studies show some discrepancies in the outcomes of cathepsin expression and activity during cancer (reviewed in [ 185 ]).…”
Section: Targeting Cathepsins In Disease Managementmentioning
confidence: 99%
“… 14 The low expression of CTSH was not conducive to the prognosis and led to a highest risk of death in patients with colorectal cancer. 15 Inversely, other investigations showed the undesirable effects of CTSH in cancers. Previous study showed the significant difference of CTSH level between lung tumor and non-tumorous tissues.…”
Section: Discussionmentioning
confidence: 99%